The charismatic leadership phenomenon in radical and militant Islamism - Ingram, Haroro J. (Religion and international security series, 2013)
Ingram journeys through over a century of history in the first full length examination of the charismatic leadership phenomenon in Islamist radicalism and militancy. Exhaustively researched and founded upon a suite of innovative multidisciplinary paradigms, this book features case studies of Hassan al-Banna, Sayyid Qutb, Abdullah Azzam, Osama Bin Laden and Anwar al-Awlaki. An authoritative analysis of a phenomenon largely ignored by scholars of both charismatic leadership and Islamism. This ground-breaking investigation offers important insights into the complex nuances that drive the rise